2015
DOI: 10.1021/acs.joc.5b00036
|View full text |Cite|
|
Sign up to set email alerts
|

Synthesis of Pyrazines from Rhodium-Catalyzed Reaction of 2H-Azirines with N-Sulfonyl 1,2,3-Triazoles

Abstract: An efficient synthetic route to a wide range of trisubstituted pyrazines is developed from Rh-catalyzed reaction of 2H-azirines with N-sulfonyl-1,2,3-triazoles through the elimination of nitrogen molecule and arylsulfinic acid. The present reaction proceeds through formation of in situ generated dihydropyrazines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(28 citation statements)
references
References 56 publications
0
28
0
Order By: Relevance
“…Interestingly,t he use of aimino rhodium(II) carbene as a[ 2C] synthon in af ormal cycloaddition reactionw as also reported. [32] As showninScheme 21, the two different products were obtained throughd ifferentm echanisms. [30] Aw ide range of triazoles 1 could be tolerated in this reactionv ery well.…”
Section: Scheme17 Synthesis Of Benzopyrrolizidine Derivativesmentioning
confidence: 99%
“…Interestingly,t he use of aimino rhodium(II) carbene as a[ 2C] synthon in af ormal cycloaddition reactionw as also reported. [32] As showninScheme 21, the two different products were obtained throughd ifferentm echanisms. [30] Aw ide range of triazoles 1 could be tolerated in this reactionv ery well.…”
Section: Scheme17 Synthesis Of Benzopyrrolizidine Derivativesmentioning
confidence: 99%
“…Nevertheless, substituted azirines are usually stable and can be stored for long periods. Over the years, significant studies have been reported on the synthesis of N‐heterocycles from azirines, including, among others, pyrazines, pyrroles, oxazoles, indoles, and imidazoles …”
Section: Introductionmentioning
confidence: 99%
“…Cycloadditions involving 2 H ‐azirines are often catalyzed by Group VIII metals. Examples include Rh I ‐catalyzed regioselective [3+3] cycloaddition and aromatization reactions of diazoindolinimines with azirines leading to indolopyrazines, Rh II ‐catalyzed [3+2] and [3+3] cycloaddition of 2 H ‐azirines with carbenes generated from transannulation and elimination of a nitrogen molecule of N ‐sulfonyl‐1,2,3‐triazoles affording a wide range of polysubstituted 3‐aminopyrroles and 1,2‐dihydropyrazines, and selective insertion reactions of arynes generated from 2‐(trimethylsilyl)aryl triflates with 2 H ‐azirines affording 2,3‐diarylindoles at 60 °C and 1,2,3‐triarylindoles at –10 °C, respectively . Ruthenium‐catalyzed intermolecular [3+2] cycloaddition of 2 H ‐azirines and activated alkynes was also reported to provide polysubstituted pyrroles in moderate to good yields .…”
Section: Introductionmentioning
confidence: 99%